Municipal weakness and crime: the case of Michoacán, Mexico - Ochoa, Jerjes Aguirre Ochoa; Torres, Hugo Amador Herrera (REVISTA QUAESTIO IURIS, 2015)
DOI: http://dx.doi.org/10.12957/rqi.2015.16913 Trabalho enviado em 17 de abril de 2015. Aceito em 25 de maio de 2015. <p class="Paragraph SCX4529407" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Abstract <p class="Paragraph SCX4529407" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX4529407" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">This article analyzes the existing relationship between legitimacy of local governments and crime in Mexico. The paper discusses the case of Michoacán, Mexico, using correlation analysis. Results establish a link between the lack of legitimacy of local governments and the crime rate. This study supports the view that the structural causes of crime and violence in Mexico are not due to the high demand of drugs in the United States, which has always existed, but to the accumulation of institutional factors which have impeded the Mexican government from enforcing the rule of law. This situation is most clearly manifested at the local level of Mexican government. <p class="Paragraph SCX4529407" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;"> <p class="Paragraph SCX4529407" style="font-weight: normal; font-style: normal; vertical-align: baseline; font-family: "Segoe UI",Tahoma,Verdana,"Sans-Serif"; background-color: transparent; color: windowtext; text-align: justify; text-indent: 0px; margin-right: 0px; font-size: 6pt;">Keywords: Organized crime, Michoacán, Drug war, legitimacy Resumo Este artigo analisa a relação existente entre legitimidade dos governos locais e crime no México. O artigo discute o caso de Michoacán, México, usando análise de correlação. Busca estabelecer uma ligação entre a falta de legitimidade dos governos locais e a taxa de criminalidade. Este estudo sustenta a visão de que as causas estruturais da criminalidade e da violência no México não são devido à alta demanda de drogas nos Estados Unidos, que sempre existiu, mas à acumulação de fatores institucionais que têm impedido o governo mexicano de fazer cumprir a institucionalidade do Estado de Direito. Esta situação se manifesta mais claramente no nível local do governo mexicano. Palavras-chave: Crime organizado, Michoacán, guerra contra as drogas, legitimidade